Quaternionic Reformulation of Generalized Superluminal Electromagnetic Fields of Dyons - Bisht, Praveen Singh (Communications in Physics, 2008)
Superluminal electromagnetic fields of dyons are described in T^4- space and Quaternion formulation of various quantum equations is derived. It is shown that on passing from subluminal to superluminal realm via quaternion the theory of dyons becomes the Tachyonic dyons. Corresponding field Equations of Tachyonic dyons are derived in consistent, compact and simpler form